Срочно нужна помощь,ребят.
Буду благодарна.
а) (c-d)^2 / сd^2+d^3 : d^2-c^2 : d^4
б) 2z-2y / (2z+2y)^3 * (2y+2z)^2 / (2y-2z)^3

1

Ответы и объяснения

  • ya2ya
  • середнячок
2013-10-02T12:24:44+04:00
1)  \frac{ (c-d)^{2}}{c d^{2}+ d^{3}  } : \frac{ d^{2}- c^{2} }{ d^{4}} = \frac{(c-d)(c-d)}{ d^{2}(c+d)} * \frac{- d^{4} }{(d-c)(d+c)} = \frac{d-c}{ (c+d)^{2}}
2) - \frac{-2z+2y}{ (2z+2y)^{3} } * \frac{ (2y+2z)^{2}}{ (2y-2z)^{3}} = \frac{-2z+2y}{ (2z+2y)^{2}(2z+2y) } * \frac{ (2y+2z)^{2}}{ (2y-2z)^{2}(2y-2z)} после сокращения одинаковых скобок = \frac{-1}{(2z+2y) (2y-2z)^{2} }= \frac{-1}{(4 y^{2}-4 z^{2})(2y-2z)}